The Influence of Learning Interest, Intrinsic Motivation, and Extrinsic Motivation on Student Achievement at SMK PGRI Enrekang - Sahade Sahade; Dewi Restika Putri; Sitti Hajerah Hasyim (Pinisi Business Administration Review, 2022)
This study aims to determine whether there is an influence or how big the influence of interest in learning, intrinsic motivation, and extrinsic motivation partially or simultaneously on student achievement in class XI Accounting SMK PGRI Enrekang. The sample of this study was all students of class XI Accounting SMK PGRI Enrekang with a total of 35 students taken by total sampling technique. Data collection techniques were carried out using questionnaires and documentation. The data analysis technique used is an instrument test consisting of validity and reliability testing, classical assumption test consisting of normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test, as well as hypothesis testing consisting of multiple linear regression, t test, test F, coefficient of partial determination and coefficient of multiple determination by using spss version 25 for windows. The results of this study concluded that interest in learning, intrinsic motivation, and extrinsic motivation partially affect the learning achievement of students in class XI Accounting at SMK PGRI Enrekang. Meanwhile, the results of the simultaneous test showed that interest in learning, intrinsic motivation, and extrinsic motivation together had a significant influence on student achievement in class XI Accounting at SMK PGRI Enrekang. the most dominant variable is extrinsic motivation. The results of this study have implications that interest in learning, intrinsic motivation, and extrinsic motivation are things that need to be considered to improve student achievement in class XI Accounting at SMK PGRI Enrekang.